Rivalry and innovation races - Martin Kukuk; Manfred Stadler (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2002)
Based on an extended game-theoretic innovation-race model, we derive some Schumpeterian hypotheses of the impact of technological rivalry, market power, technological opportunities and market size on the timing of product and process innovations. Using innovation data at the firm level in the German industrial sector, we estimate various versions of an econometric specification of the model with dichotomous innovation data by using a univariate binary probit model with qualitative regressor variables. Our empirical results are consistent with the derived hypotheses that intense rivalry, favorable technological opportunities and high demand expectations spur innovative activity, while the effect of market power is ambiguous.
urn:nbn:de:bsz:21-opus-19210
Keywords: 330; Innovation Races; Market Structure; Indirect Inference Estimation; Innovationswettbewerb; Spieltheorie; Technologiewahl; Marktstruktur; Schätzung; Deutschland